(untitled) (International Journal of Nursing Education, 2020)
Background: Patient violence behavior in psychiatric services is a challenge for health care providers. Violence behavior can affect patients themselves, other patients and staff including nurses and affect the quality of service. Psychriatic nurses can play roles in conducting risk assessment of violence behaviors to reduce impact and make appropriate decisions. Purpose: This systematic review aims to find out the factors that influence the success of psychiatric nurses in conducting risk assessment of violence behavior. Method: This systematic review begins with making questions by the PICO method, identification, eligibility, article inclusion criteria selection, screening and appraisal. Search articles through the database of Science Direct, Pubmed and Ebsco with a time span from 2009-2019. And continue with PRISMA flow diagram and JBI critique tool up to get 13 articles that relevant to be analyzed be systematic review. Result and Discussion: Reviews are carried out on articles that fit the inclusion criteria. Factors that influence the success of psychiatric nurses in conducting risk assessment of violence behavior are training and continuing education, self-confidence, understanding early warning signs/alert systems, understanding the causes of violence and the use of violence risk assessment tools) such as the Brøset Violence Checklist (BVC) and Dynamic Appraisal of situational Aggression (DASA) Conclusion: Psychiatric nurses still need continuing education and training in understanding the early signs of a patient’s violence behavior and the use of assistive devices in the form of risk assessment of violence behavior to increase the confidence of nurses and assist in making appropriate decisions.